Managing risk through the property development agreement - Calder, Alexander James (My University, 1995)
This research report analyses the effectiveness of the property development agreement as a tool in managing the risks inherent in the property development process, It incorporates an examination of a sample property development agreement and draws concluslon from market research conducted by means of a questionnaire, In Chapter 1 the property development agreement is defined, The necessity for such an aqreement is examined in Chapter 2 by identifying and describing the various stages of the property development process and by establishing the risks Inherent In each stage. Chapter 3 comprises a critical review of a typical existing development agreement. In this chapter a distinction is drawn between the "standard" clauses and those "essential" clauses which are instrumental in the allocation of the risks in property development. The agreement is then evaluated as a risk management tool and the ancillary topics of establishing those parties protected by and tnose left vulnerable by the agreement, the effects of the power and relative positions of strength of the Signatories and the enforcement of the rights arising out of property development agreements are explored. Finally, this chapter looks at some typical shortcomings of development agreements. The methodology behind the market survey is explained in Chapter 4, the responses of the sample of 50 property industry operators are analysed and concluslons are drawn from the answers to the questions posed. Chapter 5 concludes that property development agreements do exist, are necessary and are useful In creating certainty with regard to rights and obligations flowing from the property development process and that they are valuable in ensuring that risks are allocated as the parties intended they should be. This chapter also contains a checklist of items to be aware of when drafting a property development agreement and details some recommendations for possible further studies in this field.
A research report submitted to the Faculty of Architecture, University of the Witwatersrand, In partial fulfillment of the requirements for the degree of Master of Science In Building.
Keywords: Property development agreement